The transcultural nurse and the development of cultural competence - Elizabeth Castrillón Chamadoira (Universidad de Alicante, 2015)
Given the increased migration and the need for nurses to adapt to this reality, the purpose of this article is to know how to address the transcultural nursing care. The method used was based on a literature review with critical and reflective of the literature of national and international reading. The concept of cultural competence is developed and the models and theories of nursing based on intercultural communication, ethical and legal issues, institutional measures of cultural consideration and incorporating this knowledge in higher education are discussed. It concludes with the need to acquire cultural competence to facilitate the establishment of the therapeutic relationship through understanding and understanding of other cultures, valuing the context of the individual as a transcendental element.